Spatial Mapping of Facilities and Infrastructure Using GIS in Pasar Tanjung Enim Village, Muara Enim Regency - Putra, Putra; Fadhilah, Astrid (Institute of Computer Science (IOCS), 2025)
Geospatial information and community participation in regional development at various levels, including villages/subdistricts, are currently required to support economic growth and community empowerment. Good planning (based on digital and spatial information) and community participation in community management are presently needed. By utilizing digital and spatial information presented in maps and resource information, geographical locations can be easily identified. This study aims to map resources and infrastructure in Pasar Tanjung Enim Village based on geospatial information and community participation. Specifically, this research aims to provide a database and base maps of high-resolution satellite imagery and thematic maps of resources and infrastructure at the village level (large-scale and detailed), both in digital and hardcopy formats, with the involvement of community participation, and compiled into a village potential map album. Data was collected using spatial data from the Muara Enim Public Works and Spatial Planning Agency, infrastructure surveys with handheld GPS devices, and ESRI satellite imagery as base maps. Spatial data collection and field validation resulted in 148 attribute data. The results of this study are 11 thematic maps at a scale of 1:15,000, namely administrative village maps containing information on area size and boundaries, land cover, and infrastructure (road networks, telecommunications networks, government offices, places of worship, health facilities, commercial facilities, educational facilities, and public facilities). The success of this mapping supports replication in other regions. It aligns with the one map policy, emphasising spatial integration and community participation in data-driven village development.